1998
DOI: 10.1074/jbc.273.34.22068
|View full text |Cite
|
Sign up to set email alerts
|

Co-trafficking of HFE, a Nonclassical Major Histocompatibility Complex Class I Protein, with the Transferrin Receptor Implies a Role in Intracellular Iron Regulation

Abstract: The mechanism by which a novel major histocompatibility complex class I protein, HFE, regulates iron uptake into the body is not known. HFE is the product of the gene that is mutated in >80% of hereditary hemochromatosis patients. Immunofluorescence experiments indicate that they also endocytose into transferrin-positive compartments. Combined, these results suggest a role for the transferrin receptor in HFE trafficking. Cells expressing HFE have modestly increased levels of transferrin receptor and drasticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
196
3
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(217 citation statements)
references
References 26 publications
14
196
3
2
Order By: Relevance
“…Densitometric analysis revealed that during intracellular trafficking, the stoichiometric ratio between TfR and HFE remained constant at 2:1, suggesting that one HFE molecule is functionally able to affect one TfR homo-dimer. When similar pulse-chase studies were conducted using anti-HFE-C antiserum, only Endo H-sensitive HFE L was recognized, while ␤ 2 m and TfR did not co-immunoprecipitate at any time point (lanes [13][14][15], suggesting that the C-terminal tail of Endo H-resistant HFE H is not available for binding by anti-HFE-C antiserum. Our finding showed that ␤ 2 m did not co-immunoprecipitate with the non-TfR-associated, Endo H-sensitive HFE L forms, suggesting that the binding of ␤ 2 m to HFE is a prerequisite for an interaction between HFE and TfR.…”
Section: Interaction and Intracellular Transport Of Hfe And Tfrmentioning
confidence: 99%
See 1 more Smart Citation
“…Densitometric analysis revealed that during intracellular trafficking, the stoichiometric ratio between TfR and HFE remained constant at 2:1, suggesting that one HFE molecule is functionally able to affect one TfR homo-dimer. When similar pulse-chase studies were conducted using anti-HFE-C antiserum, only Endo H-sensitive HFE L was recognized, while ␤ 2 m and TfR did not co-immunoprecipitate at any time point (lanes [13][14][15], suggesting that the C-terminal tail of Endo H-resistant HFE H is not available for binding by anti-HFE-C antiserum. Our finding showed that ␤ 2 m did not co-immunoprecipitate with the non-TfR-associated, Endo H-sensitive HFE L forms, suggesting that the binding of ␤ 2 m to HFE is a prerequisite for an interaction between HFE and TfR.…”
Section: Interaction and Intracellular Transport Of Hfe And Tfrmentioning
confidence: 99%
“…11 It has been reported that by associating with TfR, HFE appears to be able to reduce the affinity of TfR for its ligand. 9,15 However, it is important to note that TfR-Tf complexes undergo rapid recycling and that the concentration of diferric Tf in blood is ෂ5 m, a value that greatly exceeds the K D of Tf for TfR. 11 In this regard, it is unlikely that the effects of HFE on TfR function are simply attributed to a reduction of Tf affinity.…”
Section: Introductionmentioning
confidence: 99%
“…The TfR2 protein is a transmembrane homodimer homolog of TfR1 and it is mainly expressed in the liver [21]. It is thought that TfR2 binds to HFE at cell surface and acts as a body iron sensor of diferric transferrin, resulting in the upregulation of hepcidin production through a not yet fully understood signalling pathway [22][23][24][25]. Concerning the novel variants in TfR2, in the case of p.Leu750Pro, proline is more hydrophilic than leucine and gives rise to a less flexible protein.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] As a common autosomal recessive genetic disorder, hereditary haemochromatosis (HH), is characterized by iron overload in the parenchymal tissue of many organs, including the pituitary, liver, pancreas, heart, endocrine organs and joints, due to increased iron absorption in the gastrointestinal tract. 5,6 The clinical consequences of iron accumulation in these organs include hypogonadism, hepatocellular carcinoma, cirrhosis of the liver, heart failure, idiopathic cardiomyopathy diabetes and arthritis, and if untreated, some cases may be fatal. 5 In 1976, HH was linked to particular human leukocyte antigen (HLA) alleles.…”
Section: Introductionmentioning
confidence: 99%